Pancho Villa, el Centauro del Norte: a historical analysis of the construction of masculinities in the Mexican Revolution. - Garnham Soto, Isidora (Revista de Historia Social y de las Mentalidades, 2025)
This article analyzes the construction of the Mexican revolutionary epic around the figure of Pancho Villa, for which it proposes, first, that the traits of masculinity were part of an identity process that rested on various cultural devices; and second, that there were different interpretations and representations of Villa of this character conforming, which nurtured the diverse masculinities that inhabited the same character. The analysis of the semantic universe that made up a "revolutionary courage" will allow us to approach the understanding of this emotion from the review of Mexican and American sources, films, corridos and the press. This research and comparison will show the different forms that the figure of Villa took that served the construction of an archetypal profile of masculinity.